BOOK REVIEW: ‟Introducere în studiul Vechiului Testament. Pentateuhul şi cărţile istorice”, Silviu Tatu (ed.), Cluj-Napoca & Oradea: Risoprint Publishing House & Casa Cărţii Publishing House, 2016, 535 p. - ȘUTEU, Ștefan (Studia Universitatis Babeș-Bolyai Theologia Catholica, 2017)
In Vetere Novum, Velatum: The New Testament is veiled in the Old Testament. The first one of the two volumes that make up the project coordinated by the Romanian exegete and Hebraist Prof. Silviu Tatu, suggestively entitled Introduction to the Study of the Old Testament, appeared as a legitimate, desirable and essential complement to the Vetero-testamentary breviarium (breviary) containing works signed by Romanian authors such as: Emilian Lemeny (Critical Introduction to the Old Testament Books), Athanase Negoiță (Old Testament Theology), Eduard Sechel (Introduction to the Old Testament), I.V. Botiza (Introduction to the Study of the Holy Scriptures), Petre Semen (Introduction to the Biblical Theology of the Old Testament), Teodor Baba (Introduction to the Study of the Old Testament), Mihai Handaric (Introduction to the Old Testament), etc.